New records of mycobiota associated with stored wheat and its by-products in Iraq (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fadhil WF, Al-Saadoon AH, Al-Moussawi FM. 2022. New records of mycobiota associated with stored wheat and its by-products in Iraq. Biodiversitas 23: 3099-3107. Wheat is a staple food for the Iraqi population and is an important feed source due to its high nutritional value. Consequently, wheat and wheat by-products are susceptible to various species of fungi during processing, transportation, or storage. In this paper, thirty-two selected fungal isolates were subjected to morphological and molecular analysis for identification through combined sequences of ITS regions, actin, calmodulin, glyceraldehyde-3-phosphate dehydrogenase, and ?-tubulin genes according to the target fungal genus. The results showed that eighteen fungal species were identified from wheat grains, flour, and bran samples collected from different silos and mills in three provinces in southern Iraq. In addition, nine species were recorded for the first time from Iraq, i.e., Alternaria consortialis, A. japonica, A. lolii, A. multiformis, A. ventricosa, Aspergillus montevidensis, Cladosporium halotolerans, C. versiforme, and Staganosporopsis tanaceti. Brief descriptions of the new records are presented. This study represents an important addition to the mycobiota of Iraq.
Keywords: Bran, flour, fungi, Iraq, wheat grains